Inspecting for positive outcomes - Bryan Livingstone (Scottish Journal of Residential Child Care)
The Care Commission was set up in 2002 to help improve care services in Scotland. It regulates almost 15,000 services that care for more than 320,000 people in all parts of Scotland. These services include childminders, foster care and adoption services, nurseries, day care services, care homes and private hospitals.